We're Going On A Bear Hunt - Michael Rosen & Helen Oxenbury
Imagine the fun of going on a bear hunt-through tall, wavy grass (SWISHY SWISHY!); swampy mud (SQUELCH SQUELCH!); and a swirling whirling snowstorm (HOOOO WOOOO!) - only to find a "real" bear waiting at the end of the trail!